Hospital management of intractable headaches. The Instituto de Neurologia de Curitiba approach - Rowe, Adriel; Iachinski, Renato; Rizelio, Vanessa; Sato, Henry Koiti; Nascimento, Maria Tereza de Moraes Souza; Souza, Ricardo Krause Martinez de; Kowacs, Pedro André (Headache Medicine, 2011)
Intractable headaches, also called refractory headaches, are usually unresponsive to standard therapies and comprise clinical conditions that represent a clinical management problem regarding therapy. Thereby, many approaches to manage "intractable headaches" have been proposed; meanwhile many aspects remain unclear and open to debate. Accordingly, these patients often require special care and customized management, such as inpatient treatment. Hospitalization aims to enhance management of the patients as a whole and thus improve their quality of life. This paper summarizes the Instituto de Neurologia de Curitiba (INC) approach, which comprises withdrawal of the overused medication, management of abstinence symptoms, management of rebound headache, introduction of effective prophylactic therapy, general counseling and education of the patient, and other aspects of management. The inpatient approach used at the INC is presented and a small sample of patients treated according to this approach is described and discussed.